4 Stat. at Large of S.C. 319–20 (1838) - (:unkn) unknown (My University, 1770)
Creating a public powder magazine and directing “That persons living in Charlestown shall store their gunpowder, except the quantity which by law they are allowed to keep in their houses…” were to be stored in the public magazines. There is no mention what that quantity was
Keywords: GUNPOWDER STORAGE